2011
DOI: 10.1002/ls.153
|View full text |Cite
|
Sign up to set email alerts
|

A COSMO‐RS based QSPR model for the lubricity of biodiesel and petrodiesel components

Abstract: The development of a new, optimised fuel is a process in which various necessary fuel properties have to be taken into account. For an inclusion of candidates not synthesised yet into the design process, a fully predictive model relying on nothing but the molecular structure is mandatory for each relevant property. One of the most important aspects for the design of a fuel is its lubricity. In this study, the predictive method conductor-like screening model for realistic solvation (COSMO-RS) for the calculatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2013
2013
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…The total and local non-stochastic, stochastic and doubly-stochastic 3D molecular linear descriptors on Minkowski atom-atom distance matrices [Eqs. (16)- (18)] were codified in an experimental version of TOMOCOMD-CARDD software (QuBiLs-MiDAS module) and calculated for the datasets mentioned above. In this work, the norm (n) and step-count (p) were ranged between 1-3 and 1-15, respectively.…”
Section: Descriptor Calculationsmentioning
confidence: 99%
See 1 more Smart Citation
“…The total and local non-stochastic, stochastic and doubly-stochastic 3D molecular linear descriptors on Minkowski atom-atom distance matrices [Eqs. (16)- (18)] were codified in an experimental version of TOMOCOMD-CARDD software (QuBiLs-MiDAS module) and calculated for the datasets mentioned above. In this work, the norm (n) and step-count (p) were ranged between 1-3 and 1-15, respectively.…”
Section: Descriptor Calculationsmentioning
confidence: 99%
“…Although 0D-2D molecular descriptors (MDs) are routinely applied in endpoint predictions, many properties have been shown to require more detailed 3D information to properly capture the relevant structural features responsible for the description or modeling of endpoints of interest [14][15][16][17][18][19][20][21][22]. It has become evident that physical, chemical, or biological properties of a compound depend on the three-dimensional (3D) arrangements of the atoms in the molecule.…”
Section: Introductionmentioning
confidence: 99%
“…Both DIN EN ISO 12156-1 and ASTM D6079 use the averaged wear scar diameter of the ball to determine the fluid's lubricity. However Fatemimoughari et al have reported that for substances with very good lubricating abilities no measurable wear could be found on the ball [8].…”
Section: Figure 6: Determination Of the Wear Scar Diameter On The Ballmentioning
confidence: 99%
“…Consequently these were screened. To gain a more detailed understanding of the properties influencing a fuels capability to reduce wear and friction in the HFRR several additional substances were also tested ( [2], [8]). In Figure 7 some of these early results are shown.…”
Section: Previous Research On Biofuel Lubricity At Ifasmentioning
confidence: 99%
“…More interestingly, in contrast to what has been observed for the two first reported QSPR approaches, the variation of the mean bubble size with the respect to ILs structure is more correctly evaluated by using this third approach as the mean bubble size follows this order: nor the correct trend for investigated halide-based ILs, the combination of ILs sigma profiles, viscosity and contact angle provides a more quantitative correlation than the approaches reported previously. As claimed by Klamt et al 23,40,41 and demonstrated by several authors, 42,43 QSPR models could be developed by using solely sigma moments, which are directly determined by the COSMOthermX software. In this case, a given property (P) could be correlated by multilinear regression of the sigma moments as follows:…”
mentioning
confidence: 97%